1986
DOI: 10.1111/j.1540-8159.1986.tb06609.x
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphous Ventricular Tachycardia and Atrioventricular Block

Abstract: Nine patients are presented who had polymorphous ventricular tachycardia (PMVT) occurring during atrioventricular (AV) block. There were five men and four women with a mean age of 80 +/- 9 years. Five patients had organic heart disease and the remaining four had primary conduction disease (bundle branch block). AV block was complete in four patients (2:1 in three, and paroxysmal in two). The mean ventricular cycle length (of the AV block rhythm) was 1567 +/- 203 ms. The mean QT interval was 0.64 +/- 0.09 s and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

1988
1988
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 8 publications
0
15
0
Order By: Relevance
“…Although this association was first described over 40 years ago (Dessertenne, 1966), remarkably little is known about the ECG predictors of this potentially lethal complication of bradyarrhythmias (Strasberg et al, 1986;Kurita et al, 1992). Indeed, the "short-long-short" series of cycles before TdP discussed below is so characteristic of diLQTS that lack of a "pause" before onset calls into question the diagnosis.…”
Section: B Bradycardiamentioning
confidence: 99%
“…Although this association was first described over 40 years ago (Dessertenne, 1966), remarkably little is known about the ECG predictors of this potentially lethal complication of bradyarrhythmias (Strasberg et al, 1986;Kurita et al, 1992). Indeed, the "short-long-short" series of cycles before TdP discussed below is so characteristic of diLQTS that lack of a "pause" before onset calls into question the diagnosis.…”
Section: B Bradycardiamentioning
confidence: 99%
“…18 Yet, during AVB, different patients develop different degrees of QT prolongation in response to similar degrees of bradycardia, 8 and it is the magnitude of this QT prolongation in response to bradycardia, rather than the bradycardia per se, that determines the risk of TdP. [6][7][8] Here, we describe how cardiac memory plays a critical role in promoting QT prolongation.…”
Section: Discussionmentioning
confidence: 99%
“…2 Yet, despite extensive experimental data explaining the pathophysiology of QT prolongation in animal models of AVB, [3][4][5] current understanding of predictors of TdP in humans is limited. [6][7][8] Although it is well established that QT prolongation, [6][7][8] particularly when accompanied by T-wave abnormalities, 8 is a requisite for TdP during AVB, we do not know why some patients develop more QT prolongation than others, despite similar bradycardia. 8 …”
mentioning
confidence: 89%
“…Kurita et al have reported that patients with bradycardia-induced torsades de pointes have abnormally long QT intervals at slow heart rates, compared with patients with bradycardia but no tachyarrhythmia (Kurita, 1992). Strasberg et al compared patients with atrioventricular block with torsades de pointes to those without torsades de pointes, and mentioned that the QT interval in patients with torsades de pointes was longer than in those without torsades de pointes, whereas heart rate and QRS interval during the escape rhythm were not significantly different (Strasberg, 1986). Moreover, they reported that QT interval above 600 ms and premature ventricular beats on electrocardiogram appear to indicate an increased risk for the development of polymorphic ventricular tachycardia in a patient with atrio-ventricular block.…”
Section: Atrio-ventricular Block -A Piece In the Puzzlementioning
confidence: 99%